If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(x + -3) = 7X + -1 Reorder the terms: (-2 + 3x)(x + -3) = 7X + -1 Reorder the terms: (-2 + 3x)(-3 + x) = 7X + -1 Multiply (-2 + 3x) * (-3 + x) (-2(-3 + x) + 3x * (-3 + x)) = 7X + -1 ((-3 * -2 + x * -2) + 3x * (-3 + x)) = 7X + -1 ((6 + -2x) + 3x * (-3 + x)) = 7X + -1 (6 + -2x + (-3 * 3x + x * 3x)) = 7X + -1 (6 + -2x + (-9x + 3x2)) = 7X + -1 Combine like terms: -2x + -9x = -11x (6 + -11x + 3x2) = 7X + -1 Reorder the terms: 6 + -11x + 3x2 = -1 + 7X Solving 6 + -11x + 3x2 = -1 + 7X Solving for variable 'x'. Reorder the terms: 6 + 1 + -7X + -11x + 3x2 = -1 + 7X + 1 + -7X Combine like terms: 6 + 1 = 7 7 + -7X + -11x + 3x2 = -1 + 7X + 1 + -7X Reorder the terms: 7 + -7X + -11x + 3x2 = -1 + 1 + 7X + -7X Combine like terms: -1 + 1 = 0 7 + -7X + -11x + 3x2 = 0 + 7X + -7X 7 + -7X + -11x + 3x2 = 7X + -7X Combine like terms: 7X + -7X = 0 7 + -7X + -11x + 3x2 = 0 The solution to this equation could not be determined.
| f(x)=[x]+n | | 3p+2q=24 | | (1/pi)(-2L+200)=0 | | 4+7x=5+x | | 834/26 | | 5x+10y=415 | | x/5+(x+3)/2=4 | | (x+5)/(2x)=3 | | ((2/4x)+9)=(3/2x) | | (4x+8)/2=(2x+5)/5 | | 11x=8x+30 | | ((2x)/5)-((4x+3)/2)=1 | | ((2x)/5)-((4x+9)/6)=2 | | ((4x)/2)+((3x+9)/6)=2 | | 11x-99=-11 | | 2x/5=(4/4)-(4x+6)/2 | | ((3x-1)/6)-((x+3)/4)=(7/12) | | 6x^2+17x+7/3x+4 | | 2x/5=(-4x+6)/2 | | 33-4x=5x+20 | | ((3x-1)/6)-((x+3)/4)=7/12 | | 1234567890qwertyuiop+9876543210asdfghjkl-1357924680zxcvbnm= | | x*x+2x+9=0 | | 29-x/4=x+5 | | 2x+14=45 | | 11=2x+y | | 5x-10=3x+3 | | -3m^2-27m=0 | | x=4x+312 | | x=14x+12 | | -132-16x+x^2=0 | | 3x*7=20x+10 |